STRATEGIC APPROACHES TO THE REVISION OF THE TAX BURDEN IN THE CONTEXT OF THE SECTORS OF THE RA ECONOMY (International Journal of Innovative Technologies in Economy, 2022)
The article discussed the strategic approaches to the revision of the tax burden in the context of the RA economy. accordingly, dynamic models were developed and evaluated, through which it is possible to identify the impact of the tax burden on the economic sectors of the economy. The assessment of the impact of the tax burden on the economic sectors was given by means of the economic-mathematical toolkit, as well as for the purpose of making objective decisions regarding the change of the tax burden. For this purpose, for the development of the sectors of the RA economy, it was proposed to review the amount of the tax burden, in particular, to implement strategic steps consisting of three stages.